2015
DOI: 10.1007/s00381-015-2832-1
|View full text |Cite
|
Sign up to set email alerts
|

Biopsy in a series of 130 pediatric diffuse intrinsic Pontine gliomas

Abstract: Stereotactic biopsies of DIPG can be considered as a safe procedure in well-trained neurosurgical teams and could be incorporated in protocols. It is a unique opportunity to integrate DIPG biopsies in clinical practice and use the biology at diagnosis to drive the introduction of innovative targeted therapies, in combination with radiotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
104
0
6

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(113 citation statements)
references
References 46 publications
3
104
0
6
Order By: Relevance
“…Moreover, even though this surgical procedure yields good results, it remains risky. In the largest series of patients, the associated mortality rate for biopsy is 1 %, and the associated morbidity rate is 5 % [40]. Thus, some parents may be reluctant to take that risk.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, even though this surgical procedure yields good results, it remains risky. In the largest series of patients, the associated mortality rate for biopsy is 1 %, and the associated morbidity rate is 5 % [40]. Thus, some parents may be reluctant to take that risk.…”
Section: Discussionmentioning
confidence: 98%
“…The inefficacy of TMZ in DIPG patients may result from the poor association of K27M expressing tumor cells with MGMT methylation, present in only 3% of tissue samples (47). Thus, this disparity highlights the importance of biological rationale for driving clinical decision making (48). A recently closed multi-center phase II clinical study has implemented the use of biopsy and molecularly aided determination of treatment with TMZ and or erlotinib based on MGMT and EGFR status ( Identifier: NCT01182350).…”
Section: Preclinical and Clinical Development Of Targeted Therapies Fmentioning
confidence: 99%
“…Due to the potential risks of the surgical procedure and poor benefit for patients, biopsy of DIPG was abandoned by the majority of neurosurgical teams in the last 20 years. However, with the development of novel molecular genetic techniques and existence of various molecular signatures which indicated for different therapeutic schemes and agents, the role of stereotactic biopsy during the treatment of DIPG was gradually refocused in the recent years (Puget et al, 2015; Carai et al, 2017). Meanwhile, studies of brainstem anatomy have revealed 12 “safe entry zones” in the brainstem, including the perioculomotor (Bricolo et al, 1991); lateral mesencephalic sulcus; suprafacial (Kyoshima et al, 1993), interfacial (Bricolo and Turazzi, 1995), and lateral (Lawton et al, 2006) sulcus limitans; periolivary; posterior median sulcus; infraclavicular and supraclavicular areas; and the peritrigeminal, infrafacial, and supratrigeminal zones (Cavalheiro et al, 2015).…”
Section: Progess In Traditional Treatments For Dipgmentioning
confidence: 99%